FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN PRODUKSI JAGUNG DI KABUPATEN SERANG - Anton Eka Prasetia; Yuli Saputra; Zaldi Dhuhana (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
Corn is one of the commodities whose trade balance is still experiencing a deficit, this indicates that interest in the development of corn is still low. One of the efforts made to increase corn production is to increase the planting area. Research Objectives To analyze the factors that influence the development of corn production and examine the problems faced by farmers in increasing corn production in Serang district. This research uses a descriptive method. Where the collected data and information is processed and analyzed and presented in a descriptive form. The data processing and analysis method used in this study uses descriptive analysis. Data obtained from farmers and related stakeholders that influence the development of corn production. The research locations are in three sub- districts which are centers of corn crops with a total of 60 farmers who are spread across three sub-districts. The research results state that the factors that influence the development of corn production in Serang Regency are the existence of government agencies, the draft agricultural management plan, especially the development of hybrid corn, the existence and interest of farmer groups and combined farmer groups to develop hybrid corn, and the arrangement of hybrid corn areas continues to be encouraged, and wide-open market opportunities. Serang District are the lack of completeness of potential hybrid corn data, the utilization of corn is still limited to physical production (seeds), the regional distribution of hybrid corn has not been conceptualized accurately and sustainably, the role assignment to farmer groups and farmers is still limited. lacking, the results of research and science and technology have not been implemented in the construction and development of hybrid corn